The ten percent thief - Lakshminarayan, Lavanya (Solaris, 2023)
"Nothing has happened. Not yet, anyway. This is how all things begin. Welcome to Apex City, formerly Bangalore, where everything is decided by the mathematically perfect Bell Curve. With the right image, values and opinions, you can ascend to the glittering heights of the Twenty Percent - the Virtual elite - and have the world at your feet. Otherwise you risk falling to the precarious Ten Percent, and deportation to the ranks of the Analogs, with no access to electricity, running water or even humanity. The system has no flaws. Until the elusive "Ten Percent Thief" steals a single jacaranda seed from the Virtual city and plants a revolution in the barren soil of the Analog world."